mAb production kinetics in CHO batch culture: exploring extracellular and intracellular dynamics - Avilan Garzon, Alejandro; Ebel, Bruno; Paris, Cédric; Schneider, Samuel; Pfister, David; Olmos, Eric (Frontiers in Bioengineering and Biotechnology, 2025)
Monoclonal antibodies (mAbs) are complex therapeutic proteins commonly produced by Chinese Hamster Ovary cell culture. Cells are cultivated using a chemically defined medium containing essential nutrients like glucose, amino acids, vitamins, etc., that cells use to grow and produce the target protein among other by-products. Various studies have focused on both extracellular and intracellular culture dynamics, measuring the concentration of various metabolites in the culture medium and inside the cell, but in the vast majority of cases these studies have excluded the intracellular concentration profile of the antibody. To better understand the complexity of the culture process, and the intracellular and extracellular dynamics of the antibody production, the present study focuses on both the extracellular and intracellular biochemical dynamics. A quenching and a lysis protocol were used to obtain the intracellular and the extracellular concentration profiles for the main substrates, metabolites, and mAb during a standard batch culture. The results revealed that three amino acids (glutamine, asparagine, and cystine) were limiting substrates as they were completely depleted almost simultaneously from the culture medium. Intracellular accumulation of different metabolites during the culture process was demonstrated, as well as a 2-day delay between the onset of the intracellular mAb production and its secretion to the culture medium. Finally, a comparison of mass transfer rates across the cell membrane, intracellular production/consumption rates, and accumulation of metabolites in the cell interior revealed that although the intracellular concentrations of the different metabolites changed during the culture process, the dynamics of these variations were much slower than the other two phenomena.